Musik dan Identitas Sosial: Analisis Perspektif Islam - Aisyah, Fitri (UIN Sunan Ampel Surabaya, 2025)
This study examines the meaning of the lyrics in Merra by the band Colorcode and how the song is interpreted by the “Wong Kalahan” community within the context of their social identity formation. In contemporary society, music is not merely entertainment but also a medium for self-reflection and social communication that represents emotional experiences and collective identity. Using a qualitative approach that combines Roland Barthes’ semiotic analysis with a hermeneutic paradigm, this research interprets the denotative, connotative, and mythical meanings embedded in the lyrics of Merra. The findings show that the lyrics convey themes of regret, loss, and the desire to correct past mistakes. For the Wong Kalahan community, these themes are understood not only as emotional expression but also as a form of muhasabah (self-evaluation) from an Islamic perspective. Values such as repentance (taubat), patience (sabr), sincerity (ikhlas), and acceptance of divine decree (qadarullah) emerge in their collective interpretation, where the experience of “losing” is viewed as a spiritually maturing test.